Pengaruh Video Wawancara dan Kisah Sukses Pengusaha terhadap Pengenalan Peluang Bisnis - Prabowo, Puji (STKIP PGRI SITUBONDO, 2024)
The Business Incubator at the University is tasked with providing support to increase the business capacity of its members. In this case, the business incubator tries to improve the ability of business owners to analyze business opportunities through video profile interviews and business success stories from entrepreneurs. This is useful for the business incubator team to be able to provide support to improve the entrepreneurial skills of business students who are developing their business to the next stage. The results of this research aim to see the influence of video interviews and entrepreneur success stories on the ability to see business opportunities. This research was conducted at one of the business incubators at the University in Bandung City, Indonesia. This research used a quantitative approach and SmartPLS to analyze data from the 205 respondents involved. The research results show that there is a significant influence of entrepreneurs' success stories on the ability of business owners to see and obtain business opportunities. However, video interviews have not shown a significant impact, so the business incubator can maximize business success stories in generating ideas so that students who have businesses can explore business potential.